A Study on the Measures for the Archival Protection of the Intangible Cultural Heritage - "Chinese Painting Pigment Making Technique" - NI, NI (Pacific International Journal, 2023)
Chinese painting pigments are essential for creating Chinese paintings and are an integral part of Chinese national culture, as they embody the spirit of Chinese painting. The technique of making Chinese painting pigments was included in the third batch of the National Intangible Cultural Heritage List by the State Council in 2011, emphasizing the significance of Chinese traditional culture. However, as a "living" culture, it is susceptible to change or extinction due to various factors such as inheritance, the social environment, and conservation measures. The art of making Chinese painting pigments is a unique art form that is primarily passed down orally. However, due to the increasing scarcity of raw materials and the decreasing number of artisan heirs, this art form is facing a challenging dilemma. In light of the current situation of Chinese painting pigment making techniques, this paper proposes several feasible solutions for archival protection. One solution is to use the regional characteristics of Chinese painting pigment making for publicity. This strategy would involve promoting the unique aspects of Chinese painting pigment making in various regions to increase awareness and appreciation of the art form. Another solution is to build an archival talent team for Chinese painting pigment technique. This approach would involve identifying and training a group of experts in Chinese painting pigment making to ensure the continued preservation and development of the art form. Finally, building an online resource for Chinese painting pigment making technique would make the information accessible to a wider audience and facilitate the dissemination of knowledge about this art form.